Who is Not Poor? Dreaming of a World Truly Free of Poverty - Pritchett, Lant (Oxford University Press on behalf of the World Bank, 2013)
When the World Bank dreams of 'a world free of poverty,' what should it be dreaming? In measuring global income or consumption expenditure poverty, the World Bank has widely adopted the $1 a day standard as a lower bound. Because this standard is based on poverty lines in the poorest countries, anyone with income or expenditures below this line will truly be poor. But there is no consensus standard for the upper bound of the global poverty line: above what level of income or expenditures is someone truly not poor? This article proposes that the World Bank compute its lower and upper bounds in a methodologically equivalent way, using the poverty lines of the poorest countries for the lower bound and the poverty lines of the richest countries for the upper bound. The resulting upper bound global poverty line will be 10 times higher than the current lower bound and at least 5 times higher than the currently used alternative lower bound of $2 a day. And in tracking progress toward a world free of poverty, the World Bank should compute measures of global poverty using a variety of weights on the depth and intensity of poverty for a range of poverty lines between the global lower and upper bounds. For instance, rather than trying to artificially force the global population of 6.2 billion (a billion is 1,000 million) into just two categories 'poor' and 'not poor,' with the new range of poverty lines the estimates would be that 1.3 billion people are 'destitute' (below $1 a day), another 1.6 billion are in 'extreme poverty' (above $1 a day but below $2 dollar a day), and another 2.5 billion are in 'global poverty' (above extreme poverty but below the upper bound poverty line).